Peran Pondok Pesantren Sebagai Lembaga Pendidikan Pembentukan Karakter Di Era Milenial (Studi Pondok Pesantren Al Utsmani) - Fajrul, Muhammad Fajrul (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This study aims to describe the role of Islamic boarding schools as character building educational institutions in the millennial era. The data collection method used in this research is through observation, interview and documentation techniques. The result of this study is that in an increasingly modern era, today's young generation is starting to lose their direction and purpose and their morals are getting worse. Islamic boarding school is the right solution as an educational institution for the formation of adolescent character. With education applied to Islamic boarding schools, it is hoped that the morals and character of teenagers will become individuals who behave well because they are the next generation of the nation and religion. Because Islamic boarding school education focuses on morals with learning through yellow books, all of their activities are required to always have a good attitude, and teachers provide examples (examples) of good deeds and words to their students in daily life, and activities that exist in the boarding school. also plays a major role in shaping the character of students